2020
DOI: 10.1371/journal.pone.0233465
|View full text |Cite
|
Sign up to set email alerts
|

Child school injury in Lebanon: A study to assess injury incidence, severity and risk factors

Abstract: Background School-based injuries represent a sizeable portion of child injuries. This study investigated the rates of school-based injuries in Lebanon, examining injury mechanisms, outcomes and associated risk factors. Methods Data were prospectively collected by intern school nurses at 11 private schools for the 2018-2019 academic year. Descriptive and inferential analyses were performed. Chisquare comparisons were conducted to determine the significance of any differences in injury rates between boys and gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
8
0
2
Order By: Relevance
“…As a result, unintentional injuries are regarded as the leading cause of death and disability among adolescents [ 7 ]. In addition to the mortalities, injuries are associated with a lifelong disability, psychosocial problems, and financial repercussions on the injured victim and their families [ 3 , 8 , 9 ]. However, this burden is disproportionately distributed, with the largest problem in low- and middle-income countries, impacting adversely on the health and productivity, and the resulting pressure on social systems [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, unintentional injuries are regarded as the leading cause of death and disability among adolescents [ 7 ]. In addition to the mortalities, injuries are associated with a lifelong disability, psychosocial problems, and financial repercussions on the injured victim and their families [ 3 , 8 , 9 ]. However, this burden is disproportionately distributed, with the largest problem in low- and middle-income countries, impacting adversely on the health and productivity, and the resulting pressure on social systems [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that different age groups are at higher risk. 6 9 11 Linakis et al showed that children aged 10 to 14 years are at higher risk for school injuries. 6 In another study, Al-Hajj et al reported that 3 to 5 years of age constituted the risk group.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, most of these studies, especially those with large samples, did not include clinical diagnoses and surgical requirement data. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] This study aimed to investigate the frequency and severity of school injuries referred to ED among school-aged children according to the Injury Surveillance Guidelines and determine clinical diagnoses and surgery requirement data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations